Análisis de competencias informacionales en médicos residentes. - Chávez-Martínez, Omar; Moctezuma-Paz, Alejandro; Sosa-Bustamante, Gloria Patricia; González, Alma Patricia; Paque-Bautista, Carlos (Revista Medica del IMSS)
Background: Information literacy skills are essential in evidence-based clinical practice, as their development enables access to, use of, and critical evaluation of scientific information. Objective: To analyze the information literacy skills of medical residents by examining their practices related to searching for, using, and evaluating scientific information. Materials and methods: An observational, cross-sectional, and analytical study was conducted among medical residents. An adapted online version of the Occupational Health Information Literacy Competency Questionnaire was administered. The study explored search strategies, use of digital tools, library services, and information evaluation criteria. Results: A total of 428 residents were analyzed, 69.6% of whom were women. Digital resources and self-directed learning predominated. Male residents demonstrated higher levels of knowledge, skills, and attitudes related to information literacy. Coming from public universities and being enrolled in adult-focused specialties were associated with greater use of on-site or home loan library services. Third-year residents and above more frequently used databases such as PubMed and Cochrane for information retrieval. Conclusions: Medical residents’ information literacy was characterized by a predominance of self-directed learning, with male residents showing higher proficiency in knowledge, skills, and attitudes. The implementation of institutional information literacy programs is recommended.